ANALISIS SIKAP ILMIAH MAHASISWA DIPROGRAM STUDI PENDIDIKAN BIOLOGI FKIP UNIVERSITAS RIAU TAHUN AKADEMIS 2014/2015 - Rina Fitria; Yuslim Fauziah; Arnentis Arnentis (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Has conducted a descriptive study aims to provide an overview of the scientific attitude of students on the course in the Aquatic Ecology Studies Program Riau University Biology Education Academic Year 2014/2015. The samples were students of Biology Education FKIP Riau University who took a course Aquatic Ecology Academic Year 2014/2015 amounted to 99 people. Parameter research is the scientific attitude indicators: an attitude of curiosity, collaboration, conscientious, honest, critical and responsible attitude. Data was collected using observation sheets, scientific attitude in the four meetings in the course Aquatic Ecology. The results showed that the attitude of scientific curiosity at every meeting is 74.12 - 77.69% to the category of good, conscientious attitude to every meeting is 72.47 - 80.30% with the good category, the attitude of responsibility is 73.23 - 77.78% good category, cooperative attitude of students is 75.51 - 89.65% excellent category, a critical stance is 73.23 - 77.53% categorized as good and honest attitude of students at each meeting is 73.23 - 76.52% with the good category. It can be concluded that the scientific attitude of students with the good category. Keywords :Scientific Attitude, AquaticEcology